The glasgow prognostic score. An useful tool to predict survival in patients with advanced esophageal squamous cell carcinoma - Henry, Maria Aparecida Coelho de Arruda [UNESP]; Lerco, Mauro Masson [UNESP]; Oliveira, Walmar Kerche de [UNESP]; Guerra, Anderson Roberto [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP] (Acta Cirúrgica Brasileira, 2015)
To evaluate the usefulness of the Glasgow Prognostic Score (GPS) in patients with esophageal carcinoma (EC). A total of 50 patients with EC were analyzed for GPS, nutritional and clinicopathologic parameters. Patients with CRP ≤ 1.0mg/L and albumin ≥ 3.5mg/L were considered as GPS=0. Patients with only CRP increased or albumin decreased were classified as GPS=1 and patients with CRP > 1.0mg/L and albumin < 3.5mg/L were considered as GPS=2. GPS of 0, 1 and 2 were observed in seven, 23 and 20 patients, respectively. A significant inverse relationship was observed between GPS scores and the survival rate. The survival rate was greatest in patients with GPS= 0 and significantly higher than those from patients with GPS=1 and GPS=2. Minimum 12-month survival was observed in 71% patients with GPS=0 and in 30% patients with GPS=1. None of the patients with GPS=2 survived for 12 months. A significant relationship between CRP or albumin individually and the survival rate was observed. No significant relationship among nutritional, clinic pathological parameters and survival was found. Glasgow Prognostic Score is an useful tool to predict survival in patients with esophageal carcinoma.
Keywords: Esophageal Neoplasms; Neplasms; Squamous Cell; Glasgow Outcome Scale